2003
DOI: 10.1016/s0014-5793(03)00506-4
|View full text |Cite
|
Sign up to set email alerts
|

In situ photoaffinity labeling of the target protein for lembehyne A, a neuronal differentiation inducer

Abstract: A C 36 linear acetylene alcohol, lembehyne A (LB-A), induces neuronal di¡erentiation against neuroblastoma cells morphologically and also functionally. The di¡erentiation and cytostatic e¡ect induced by LB-A was speci¢c to neuroblastoma, Neuro 2A cells. To identify the target protein for LB-A, a radioactive photoa⁄nity probe, [125 I]18-(2P P-azido-5P P-iodo-benzoyloxy)-LB-18 ([ 125 I]azido-LB-18), was synthesized. As a result of in situ labeling experiments against Neuro 2A cells, a protein of M r 30 kDa was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
0
10
1
Order By: Relevance
“…Many authors have reported that long-time treatment (24-48 h) with several sponge crude extracts induces alterations of cell morphology and microtubule organization (41,42,46). In the present conditions, membrane alterations were a more precocious event than that observed by other studies (18,42); for this reason, we hypothesize that A. oroides extract might specifically modify cytoskeletal proteins but further analyses are needed.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Many authors have reported that long-time treatment (24-48 h) with several sponge crude extracts induces alterations of cell morphology and microtubule organization (41,42,46). In the present conditions, membrane alterations were a more precocious event than that observed by other studies (18,42); for this reason, we hypothesize that A. oroides extract might specifically modify cytoskeletal proteins but further analyses are needed.…”
Section: Discussioncontrasting
confidence: 50%
“…Recently, it has been reported that Petrotetrayndiol A, a polyacetylene isolated from the sponge Petrosia sp., induced caspase-dependent apoptosis in SK-MEL-2 human melanoma cells (40), Lembehyne A, from Haliclona sp., led differentiation of Neuro 2A cells (41) and Labuanine A, from Biemna fortis, caused in Neuro 2A cells multipolar neuritogenesis and arrested cell cycle at the G2/M phase (42). Many studies in the scientific literature have therefore investigated the effects of isolated molecules from sponge extracts on murine and less frequently on human neuroblastoma cells (43).…”
Section: Discussionmentioning
confidence: 99%
“…This linear C 36 diacetylenic alcohol induces neuritogenesis in Neuro 2A neuroblastoma cells resulting in bipolar neuritis [356]. A photoaffinity probe based on 33J, [ 125 I]-azido-LB-18, specifically labeled in vivo a 30-kDa protein in Neuro 2A cells that is anticipated to be the target of 33J [357]. The presence of a (3R)-propargylic alcohol on a minimally C 18 alkyl chain were necessary for strong neuritogenic activity [358].…”
Section: Marine Fatty Acids Andmentioning
confidence: 99%
“…A similar linear polyacetylene alcohol (36 carbons) named lembehyne A found in Indonesian marine sponge Haliclona sp. (Aoki et al, 2001) exhibited the ability to induce neuronal differentiation in neuroblastoma cells (Aoki et al, 2003). Newly synthesized LB-18, closely related to lembehyne A has been shown to induce p21/WAF1 and cause G1 phase arrest in mouse neuroblastoma Neuro2A cells and thus cause cell death in human neuroblastoma KP-N-TK cells in a dose-dependent manner (Ozimi et al, 2006).…”
Section: Alcohols With Both Double and Triple Bondsmentioning
confidence: 99%